Rancang Bangun Kendali AC Laboratorium Komputer Prodi Teknik Informatika Menggunakan Arduino Berbasis Website - Hida Jaya Habibi; Nur Cholik Hasyim; Muh. Nur Hariri (Jurnal Pengelolaan Laboratorium Pendidikan, 2021)
Inside a Computer Laboratory, AC is a tool needed to cool the room. But its use is sometimes we often forget to turn off the air conditioner after completed practicum. So that the Pranata Laboratorium Pendidikan (PLP) must check one by one the AC in each laboratory whether it has been turned off or not. This leads to wasteful use of electricity and reduce the service life of the air conditioner. In this research method, we build tools that control and monitor the air conditioning remotely through a Website site. This tool uses an Arduino as a microcontroller, nodemcu for Internet conection adapter, an infrared sensor to send commands to the air conditioner and the light sensor to determine the condition of the AC on or off. Conclusions obtained by this tool computer lab technicians do not need to go into any Laboratory for make sure the AC is turned on or off.By accessing this Websitesite, technicians can control the AC remotely and also monitor the condition of the AC on or off.